Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

Katlyn99

  • 3 years ago

Using substitution to solve the system x = 2y + 3 and 4x - 5y = 9, which of the following could be the first step? x - 2y = 3 4x - 5y = 9 4(2y + 3) - 5y = 9 x + 2y = 4x - 5y 5x - 3y = 12 - 3x + 7y = -6

  • This Question is Closed
  1. campbell_st
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    ok... you are told x = 2y + 3 you need to substitute this into the equation 4x - 5y = 9 so replace x with 2y + 3 you would have 4(2y + 3) - 5y = 9

  2. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy